Basis of Peruvian Maritime Sovereignty up to 200 Miles - Ferrero Costa, Eduardo (1974)
In 1947, Supreme Decree 781 declared Peru's sovereignty over 200 miles. This action was the cause of different positions on the international level and the beginning of a new debate. The objective of this article is to analyze the foundations of maritime sovereignty up to 200 nautical miles. In this regard, they are examined from a scientific point of view, highlighting the economic and social aspects, and from a legal point of view, indicating the inherent rights that belong to the coastal states and how they can be exercised within this new territory. By defining maritime sovereignty through these aspects, it is concluded that its validity is rooted in its international influence and recognition.